2016
DOI: 10.1016/j.jvir.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival after Radiofrequency Ablation of Lung Oligometastases from Five Types of Primary Lesions: A Retrospective Evaluation

Abstract: Data from this single-center study appear promising in terms of long-term survival after RF ablation of lung oligometastases from 5 primary lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
0
15
1
Order By: Relevance
“…There were 34 studies[ 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 ] identified in this network meta-analysis [ Figure 1 ]. These included 17 studies from Europe/America and 17 studies from East Asia.…”
Section: Resultsmentioning
confidence: 99%
“…There were 34 studies[ 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 ] identified in this network meta-analysis [ Figure 1 ]. These included 17 studies from Europe/America and 17 studies from East Asia.…”
Section: Resultsmentioning
confidence: 99%
“…Extrahepatic metastasis is one of the most important predictors of poor OS 9 , 10 . Several studies have investigated therapies for oligometastases, with promising results 11 - 13 . Niibe et al reported a 2-year OS rate of 65.7% in patients with pulmonary oligometastases 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Most series evaluating RFA for metastatic disease report local progression rates of 10-30%, especially for lesions larger than 3 cm [14,18,63,[69][70][71]. Omae et al [72] reported longterm follow-up in 123 patients with lung oligometastases treated with RFA. The authors found a 5-year OS rate and recurrencefree survival rate of 62% and 25% [72].…”
Section: Metastatic Diseasementioning
confidence: 99%
“…Omae et al [72] reported longterm follow-up in 123 patients with lung oligometastases treated with RFA. The authors found a 5-year OS rate and recurrencefree survival rate of 62% and 25% [72].…”
Section: Metastatic Diseasementioning
confidence: 99%